2021
DOI: 10.1039/d1ta03399a
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining pronounced proton transportation of solid oxides prepared with a sintering additive

Abstract: Proton-conducting electrolytes (PCEs) have led to significant advances in the fields of solid-state ionics, energy conversion and high-temperature electrochemistry, providing the basis of various solid oxide devices that demonstrate outstanding...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…It should be mentioned that the addition of 0.5 wt% CuO has no significant effect on the cell parameters, as we have previously shown in the article. 40 In general, the bulk transport properties of electrolytes depend on the impurity type introduced, in particular, its ionic radius and charge state. According to this view, the structural parameters upon Zr-to-Sn substitution should not have a significant effect on the transport properties of the ceramic materials.…”
Section: Structural Characterization Of Bzssmentioning
confidence: 99%
“…It should be mentioned that the addition of 0.5 wt% CuO has no significant effect on the cell parameters, as we have previously shown in the article. 40 In general, the bulk transport properties of electrolytes depend on the impurity type introduced, in particular, its ionic radius and charge state. According to this view, the structural parameters upon Zr-to-Sn substitution should not have a significant effect on the transport properties of the ceramic materials.…”
Section: Structural Characterization Of Bzssmentioning
confidence: 99%
“…The effect of this type of sintering additive on the low-temperature transport properties of barium stannates was previously studied by Mineev et al [34], who confirmed that the introduction of 0.5 wt% CuO results in the point distribution of a Cu-based phase along the grain boundaries. Although the volume concentration of this phase did not exceed 3%, this turned out to be sufficient for the formation of free (or incompletely covered with CuO) grain boundaries (Fig.…”
Section: Microstructural Featuresmentioning
confidence: 68%
“…The main theme of this work is the evaluation of transport properties of the Sc-doped BaSnO 3 materials at high temperatures. Previously, the bulk and grainboundary conductivities were thoroughly studied for a similar system by the alternating current (AC) impedance spectroscopy [34]. It was found that at temperatures above 350 ℃, the total σ of stannates is determined by the bulk component.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…The remaining parts of the low-frequency stand for the electrode process and no elaborate split. 12 However, the acquisition of conductivity is not affected. In Figure 3b, the first semicircle of BCSDCu is determined as a grain-boundary process based on the characteristic capacitance (2.73 × 10 −8 F), frequency (9.78 × 10 2 Hz), and the DRT peak locations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%